COMMUNITY AWARENESS AND ITS IMPACT ON TOURISM INFRASTRUCTURE DEVELOPMENT IN THE COASTAL AREA OF KAMPUNG TUA NONGSA PANTAI - Nursyamsu, Lathifa; Fidya Nasywa Rahmad; Alifianty Salsabila; Nabilla Putri Adinda; Jihan Fahira; Anasaqina Farhanna Putri (Program Sarjana Arsitektur Universitas Internasional Batam, 2025)
This study explores the influence of community awareness on the development of tourism infrastructure in Kampung Tua Nongsa Pantai, a coastal heritage village in Batam, Indonesia. Despite its strategic location and rich cultural assets, the area faces challenges in infrastructure development due to limited funding, environmental degradation, and community resistance rooted in cultural preservation concerns. Using a qualitative descriptive approach, data were collected through observations, semi-structured interviews, and document analysis. The findings indicate that community awareness plays a dual role: it can either support or hinder infrastructure development, depending on the perceived alignment with local values and identity. While some residents, particularly elders, expressed concerns about cultural erosion, others, including local leaders and youth, supported infrastructure improvements to enhance tourism opportunities. The study also identified major infrastructure deficiencies such as unsafe access routes, lack of public amenities, and poor waste management. Despite these challenges, grassroots efforts—such as clean-up campaigns and cultural micro-enterprises—demonstrate a growing community commitment to sustainable tourism. This research contributes to the literature on community-based tourism by highlighting the importance of cultural sensitivity and inclusive planning in infrastructure development. Limitations of this study include its focus on a single case study and the constraints of qualitative generalizability. Future research should explore comparative studies across multiple coastal regions and integrate quantitative methods to broaden insights. The study concludes that sustainable tourism development requires not only physical infrastructure but also active and culturally grounded community engagement.